Mechanisms of the Incretin Effect in Subjects with Normal Glucose Tolerance and Patients with Type 2 Diabetes - Mari, Andrea; Bagger, Jonatan I.; Ferrannini, Ele; Holst, Jens J.; Knop, Filip K.; Vilsbøll, Tina (PloS one, 2013)
The incretin effect on insulin secretion was investigated in 8 subjects with type 2 diabetes (T2D) and 8 with normal glucose tolerance (NGT), using 25, 75, and 125 g oral glucose tolerance tests (OGTT) and isoglycemic intravenous glucose infusions (IIGI). The ß-cell response was evaluated using a model embedding a dose-response (slope=glucose sensitivity), an early response (rate sensitivity), and potentiation (time-related secretion increase). The incretin effect, as OGTT/IIGI ratio, was calculated for each parameter. In NGT, the incretin effect on total secretion increased with dose (1.3 ± 0.1, 1.7 ± 0.2, 2.2 ± 0.2 fold of IIGI, P<0.0001), mediated by a dose-dependent increase of the incretin effect on glucose sensitivity (1.9 ± 0.4, 2.4 ± 0.4, 3.1 ± 0.4, P=0.005), and a dose-independent enhancement of the incretin effect on rate sensitivity (894 [1145], 454 [516], 783 [1259] pmol m(-2) L mmol(-1) above IIGI; median [interquartile range], P<0.0001). The incretin effect on potentiation also increased (0.97 ± 0.06, 1.45 ± 0.20, 1.24 ± 0.16, P<0.0001). In T2D, the incretin effect on total secretion (1.0 ± 0.1, 1.1 ± 0.1, 1.3 ± 0.1, P=0.004) and glucose sensitivity (1.2 ± 0.2, 1.3 ± 0.2, 2.0 ± 0.2, P=0.005) were impaired vs NGT; however, the incretin effect on rate sensitivity increased already at 25 g (269 [169], 284 [301], 193 [465] pmol m(-2) L mmol(-1) above IIGI; negligible IIGI rate sensitivity in T2D prevented the calculation of the fold increment). OGTT did not stimulate potentiation above IIGI (0.94 ± 0.04, 0.89 ± 0.06, 1.06 ± 0.09; P<0.01 vs NGT). In the whole group, the incretin effect was inversely associated with total secretion during IIGI, although systematically lower in T2D. In conclusion, 1) In NGT, glucose sensitivity and potentiation mediate the dose-dependent incretin effect increase; 2) In T2D, the incretin effect is blunted vs NGT, but rate sensitivity is enhanced at all loads; 3) Relatively lower incretin effect in NGT is associated with higher secretion during IIGI, suggesting that the reduced incretin effect does not result from ß-cell dysfunction.